Evaluation of alternative organizational and technological solutions for temporary supporting damaged structures based on multi-criterion decision-making methods - BOZHYNSKYI, Mykhailo; HAIEVA, Kateryna (Ways to Improve Construction Efficiency, 2025)
The article addresses the problem of improving organizational and technological solutions for temporary shoring of damaged structures in cases of accidental failures caused by impacts not anticipated at the design stage. It emphasizes that timely and efficient temporary shoring is a critically important stage that ensures the structural stability of a building prior to the implementation of permanent repair works. Traditional approaches to the selection of technologies have predominantly relied on single-factor technical inspections, which do not fully account for the complexity, contradictions, and multi-criteria nature of the task. At the same time, recent scientific developments in the field of construction demonstrate a transition towards the application of multi-criteria decision-making (MCDM) methods, which make it possible to develop transparent, well-founded, and reproducible selection algorithms. The aim of the study is to test the potential of MCDM for assessing alternative methods of temporary shoring and identifying the most effective solutions considering technical, organizational, and technological factors. The paper proposes a hierarchical structure of criteria covering more than forty parameters, characterizing safety, cost, duration, resource availability, degree of mechanization, and logistical constraints. Particular attention is given to the methods of determining the weights of criteria, ranging from classical pairwise comparison procedures (AHP) to group expert evaluations with consistency verification. For further ranking of alternatives, the TOPSIS method was applied, enabling the assessment of the relative closeness of actual shoring alternatives to the ideal solution. The practical value of the research lies in the application of the proposed methodology to four real-world scenarios of temporary shoring of damaged reinforced concrete roof structures of industrial buildings. The analysis of results demonstrated that the most effective option is the combination of using a mounting platform with an information-mathematical system for optimizing the shoring process, which minimizes enterprise downtime and enhances the reliability of construction works. The study also applied fuzzy evaluations and linguistic scales to incorporate qualitative parameters, which strengthen the adaptability of the approach under conditions of uncertainty. The conclusions emphasize that the integration of AHP and TOPSIS provides an effective toolkit for developing well-substantiated decisions in the field of emergency construction. The methodology can be applied to standardize decision-making processes in emergency situations, to prepare methodological guidelines for construction organizations, and to develop specialized software tools for engineering decision support. The results confirm the potential of multi-criteria methods for optimizing organizational and technological solutions aimed at eliminating the consequences of accidental structural failures, thereby improving the efficiency and safety of construction processes.